MOTIVATION AND ITS RELATIONSHIP WITH ESSAY WRITING ACHIEVEMENT IN THE HIGHER EDUCATION LEVEL - Jeane Theresia Limeranto; Concilianus Laos Mbato (Eltin Journal : Journal of English Language Teaching in Indonesia, 2022)
Writing is usually considered the most challenging skill to be mastered for Indonesian EFL students. Consequently, they may experience a lack of motivation in the writing process, which might influence their writing achievement. Therefore, this study was conducted to investigate the level of students’ writing motivation, the relationship between their motivation, factors affecting students’ motivation in essay writing and achievement in writing, and the effective strategies they use to improve their writing motivation. This study utilized a mixed-method research design which involved 25 students who took essay writing class. The instruments employed were questionnaire and interviews. The result of quantitative data analysis showed that there was a positive correlation between students’ motivation and their achievement in essay writing (r (23) = .304 p <.05). It indicated that the students who had higher motivation in writing displayed a higher level of writing performance. While qualitative study revealed some factors that impeded students’ writing motivation and writing achievement, namely the lack of teachers’ effective teaching methods and attitudes and the lack of students’ linguistic competence. This study offers useful implications toward teaching and further research.